Predictors for adherent behavior in the COVID-19 pandemic: A cross-sectional telephone survey - Andrea Siebenhofer; Andrea Siebenhofer; Clemens Könczöl; Klaus Jeitler; Klaus Jeitler; Daniela Schmid; Phillip Elliott; Alexander Avian (Frontiers Media S.A., 2022)
BackgroundDuring the COVID-19 pandemic, protective measures have been prescribed to prevent or slow down the spread of the SARS-CoV-2 virus and protect the population. Individuals follow these measures to varying degrees. We aimed to identify factors influencing the extent to which protective measures are adhered to.MethodsA cross-sectional survey (telephone interviews) was undertaken between April and June 2021 to identify factors influencing the degree to which individuals adhere to protective measures. A representative sample of 1,003 people (age >16 years) in two Austrian states (Carinthia, Vorarlberg) was interviewed. The questionnaire was based on the Health Belief Model, but also included potential response-modifying factors. Predictors for adherent behavior were identified using multiple regression analysis. All predictors were standardized so that regression coefficients (β) could be compared.ResultsOverall median adherence was 0.75 (IQR: 0.5-1.0). Based on a regression model, the following variables were identified as significant in raising adherence: higher age (β = 0.43, 95%CI: 0.33-0.54), social standards of acceptable behavior (β = 0.33, 95%CI: 0.27-0.40), subjective/individual assessment of an increased personal health risk (β = 0.12, 95%CI: 0.05-0.18), self-efficacy (β = 0.06, 95%CI: 0.02-0.10), female gender (β = 0.05, 95%CI: 0.01-0.08), and low corona fatigue (behavioral fatigue: β = −0.11, 95%CI: −0.18 to −0.03). The model showed that such aspects as personal trust in institutions, perceived difficulties in adopting health-promoting measures, and individual assessments of the risk of infection, had no significant influence.ConclusionsThis study reveals that several factors significantly influence adherence to measures aimed at controlling the COVID-19 pandemic. To enhance adherence, the government, media, and other relevant stakeholders should take the findings into consideration when formulating policy. By developing social standards and promoting self-efficacy, individuals can influence the behavior of others and contribute toward coping with the pandemic.